Distance Mathematics Teaching and Academic Performance in Morocco - El Abbadi, Salwa; Hafidi Alaoui, Moulay Ismail (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
In this article, we discuss the academic performance and impact of distance teaching of mathematics in the Moroccan education system. This educational science research, based on exploratory thinking, aimed to show the impact and challenges of distance teaching of mathematics within the Moroccan education system through examining this fundamental question: How could school programs, pedagogical organization, and the performance of pupils and teachers in Morocco best address the challenges of distance teaching of mathematics? The answer is based on a qualitative analysis of the content of the documentation that frames the teaching-learning process and the evaluation of mathematics in Morocco and, on the other hand, on the projection of research hypotheses in the field through various strategies inspired by our research objectives.